Multi-Criteria Analysis Of Offshore Wind Energy Site Suitability In North Carolina - Gregg, Kelsey Lauren (East Carolina University, 2015)
There is growing social, political, and economic interest in developing renewable energy technologies in an effort to create a more sustainable and secure energy market. Wind energy has potential to satisfy energy needs with fewer negative impacts than conventional energy production. North Carolina has some of the greatest offshore wind potential in the US; however, a multitude of barriers prevent the construction of wind farms. Planners must consider a variety of exclusion variables when deciding where to allow development, including environmental, economic, and socio-political factors. The Bureau of Ocean Energy Management first released potential leasing blocks totaling approximately 474,016 hectares, based on applicable exclusion variables to gauge stakeholder interest and opinion. Based on responses, official Wind Energy Areas (WEAs) were defined. At 124,477 hectares, the WEAs are remarkably smaller than the original call areas, greatly limiting NC's potential in this new market. However, many of the variables limiting the WEAs have mitigation potential allowing for expansion of offshore wind. This study utilizes public comment data and GIS layers for key exclusion variables used to define WEAs. By treating variables of interest as distinct layers, GIS was used to identify variations in the suitability in the ocean space off North Carolina's coastline. By analyzing wind feasibility while taking into consideration site-specific mitigation techniques, four site suitability maps were developed: environmental, economic, social, and overall site suitability. Policy-makers and planners in NC can use these maps in the future to mitigate inherently local variables and to inform communication strategies that build public acceptance of offshore wind development, further improving chances of successful implementation.
Keywords: Geography; Natural resource management; Environmental studies; Marine spatial planning; Offshore wind energy; Offshore wind power plants--Environmental aspects--North Carolina; Offshore wind power plants--Economic aspects--North Carolina; Offshore wind power plants--North Carolina--Sociological aspects; Offshore wind power plants--Political aspects--North Carolina; Wind power--North Carolina; Renewable energy sources--North Carolina